TINJAUAN LITERATUR: TANTANGAN KEAMANAN PANGAN DAN GIZI DI LINGKUNGAN PERKOTAAN: Literature Review: Food And Nutrition Security Challenges In Urban Environments - Prameswari, Rara Ayuning; Nazwa Aulia; Putri Zakiyatun Nufus; Septa Indra Puspikawati (Calvaria Medical Journal, 2026)
Background: Rapid urbanization has transformed food systems and consumption patterns in urban areas. Vulnerable groups face economic, environmental, and social barriers in accessing safe and nutritious food, a condition further aggravated by the COVID-19 pandemic. Objectives: To identify determinants of urban food security and nutrition, analyze the most vulnerable groups, and describe recommended strategies and interventions. Methods: A systematic literature review was conducted using the PRISMA 2020 guidelines with searches on Google Scholar. Of 432 articles identified, 9 articles met the inclusion criteria and were analyzed. Results: Economic factors, food environment, urbanization, and social and institutional factors are the main determinants of urban food security. The most vulnerable groups include low-income households, female-headed households, renters, and residents of informal settlements. The COVID-19 pandemic worsened food insecurity through income loss and supply chain disruptions. Recommended strategies include strengthening local food production, food diversification, improving distribution systems, social protection, and improving the urban food environment. Conclusions: Urban food security is a multidimensional issue requiring an integrated and multisectoral approach involving the food, health, social, economic, and spatial planning sectors.